Food taboos among pregnant women and associated factors in eastern Ethiopia: A community-based cross-sectional study. (November 2022) - Amare, Wbalem; Tura, Abera Kenay; Semahegn, Agumasie; Teji Roba, Kedir
Objective: The main aim of this study was to assess food taboos and associated factors among pregnant women in eastern Ethiopia. Methods: A community-based cross-sectional study was conducted among randomly selected 422 pregnant women at Haramaya Demographic Surveillance System from Haramaya District, eastern Ethiopia. Data on sociodemographic conditions, the presence of food taboos, and perceived reasons were collected using the face-to-face interview method by trained data collectors through arranged home visits. Collected data were entered into EpiData 3.1 and exported to statistical package for social sciences version 23 for cleaning and analysis. Descriptive, binary, and multiple logistic regression analyses were carried out to determine the relationship between explanatory and outcome variables. Adjusted odds ratio (AOR) with 95% confidence interval (CI) at p value less than 0.05 was used to declare significant association. Results: Approximately half (48%, 95% CI: 43%, 52%) of the pregnant women reported the presence of pregnancy-related food taboos. Pregnant women who have heard about food taboos (AOR: 3.58; 95% CI: 1.89, 6.83), pregnant women had friends who avoided food (AOR: 1.91; 95% CI: 1.22, 2.99), women's monthly income ⩽840 ETB (AOR: 1.73; 95% CI: 1.10, 2.73), and pregnant women who had not attended formal education (AOR: 1.95; 95% CI: 1.18, 3.23) were more likely to report food taboos. The odds of pregnant women who had attended uptake of immunization services were less likely to have food taboos (AOR: 0.35; 95% CI: 0.21, 0.58). Conclusion: Pregnancy-related food taboos among pregnant women are unacceptably high. Therefore, awareness creation and nutritional counseling at health service delivery points are imperative actions for pregnant women to avoid food taboos norms. Further research should be done to understand the social and cultural ground of food taboos during pregnancy.